2010
DOI: 10.1371/journal.pmed.1000345
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chest Physiotherapy in Infants Hospitalized with Acute Bronchiolitis: A Multicenter, Randomized, Controlled Trial

Abstract: Vincent Gajdos and colleagues report results of a randomized trial conducted among hospitalized infants with bronchiolitis. They show that a physiotherapy technique (increased exhalation and assisted cough) commonly used in France does not reduce time to recovery in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
2
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 29 publications
3
71
2
9
Order By: Relevance
“…[145][146][147][148] Since that review, a study 149 of the passive expiratory technique found a small, but significant reduction in duration of oxygen therapy, but no other benefits.…”
Section: Figurementioning
confidence: 99%
“…[145][146][147][148] Since that review, a study 149 of the passive expiratory technique found a small, but significant reduction in duration of oxygen therapy, but no other benefits.…”
Section: Figurementioning
confidence: 99%
“…Gajdos et al 25 , conducted a multicenter clinical trial in 496 infants using the forced expiratory technique, this study showed no benefits of the CP but the primary end point was the time of randomization to the recovery of these patients. It is very important to emphasize that the forced expiratory technique should be avoided in children under 24 months of age due to high compliance tracheal and chest, because the rapid chest compression promotes an interruption of expiratory flow 26 thus demonstrating the importance of creating a modulated flow so that there is an appropriate extension of the expiratory phase and a subsequent clearance of the distal airways.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled studies have demonstrated no benefit from increased-exhalation technique on hospital stay or cardiorespiratory parameters in severe acute viral bronchiolitis. [41][42][43] In addition, side effects have been observed (vomiting, transient respiratory dysfunction, bouts of hypotonia), requiring interruption of the procedure. Rib fracture and mechanical drawbacks such as tracheal collapse leading to air and secretion trapping have also been observed.…”
Section: Chest Physical Therapymentioning
confidence: 99%
“…CPT may delay or prevent the need for mechanical ventilation and may result in fewer complications, but the study was unable to demonstrate such outcomes, as the study did not have sufficient power. Also, the Gajdos et al study 41 and the Rochat et al study 53 have identified patient subgroups whose auscultation was improved by this treatment. This improvement would be due to the absence of atopic background.…”
Section: Chest Physical Therapymentioning
confidence: 99%